Voluntary intake and productive performance of female buffaloes with a new pre-mixture adjusted to their nutritional requirements - Gutiérrez, Odilia; Cairo, Juan; Ramírez, B.; Dorta, Natacha; Vasallo, George; Valera, Moises (Cuban Journal of Agricultural Science, 2014)
In order to determine the productive behavior of water female buffaloes, supplemented with a mineral pre-mixture, two studies were carried out at the cattle enterprise “La Bayamesa”, from Bayamo, Granma province. In the first study, 30 female buffaloes from unit 1 were used, through a completely randomized design, and were divided into two groups: one of control that received 400 g of Norgold and an experimental group, which was offered 400 g of Norgold, plus 100 g of a mineral pre-mixture. In the second study, four units with 30 female buffaloes each were used, and the procedure was similar to the first one. Milk production was measured in the 100 % milking animals. There were no differences among treatments for the intake of dry matter. The values ranged between 16 and 19 kg/animal/d, and the mean digestibility was 48 %. There was an increase in the digestibility of crude protein and milk production was favorable for animals that received the mineral supplementation. The results demonstrated that mineral supplementation increases nutrient digestibility and milk production in female water buffaloes under the conditions of this study Key words: female buffaloes, minerals, milk production